COMPETING IN A GLOBAL ENVIRONMENT: THE VALUE OF INTERNATIONAL QUALIFICATION OF POTENTIAL MANAGERS ACROSS OWNERSHIP STRUCTURE - Santiago, Andrea L. (Philippine Management Review, 2009)
Regardless of how we view globalization, its consequence is the meeting of cultures and the desire to share not only the experience but the goods and services as well. Presumably in this environment there will be greater motivation for local businesses to invest in managers who already have the international exposure to shorten the learning curve. This investment is reflected in a compensation premium. Consequently, if businesses in the Philippines are willing to pay a compensation premium for international exposure, then the marketability of an individual naturally increases. This study compares the perception about international qualification across differing ownership structures paying particular attention to the local family business.
Keywords: international degree, family business, managerial selection, compensation study